Dinamika Komunitas Gulma pada Sistem Tumpang sari Jagung dan Kacang Hijau Hubungannya dengan Produktivitas Lahan - S. Kusmiyati; N. Setyowati; E. Turmudi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Kusmiyati S, Setyowati N, Turmudi E. 2020. The dynamics of weed communities and land productivity in intercropping corn and green bean. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Intercropping increases the productivity of plants through land efficiency. The types of weeds grow in intercropping are different from that of monocultures. This study aims to identify the type and number of weeds on intercropping corn and green beans and describe the relationship between weed competition and the productivity of corns and green beans. The study was conducted in September 2018 until January 2019 at Pematang Gubernur, Bengkulu, using a Randomized Complete Block Design. Corn spacing in intercropping was 60 cm x 30 cm, 90 cm x 30 cm, and 120 cm x 30 cm as well as 60 cm x 30 cm in monoculture while green bean spacing was 30 cm x 30 cm. The main variable data were collected and analyzed using analysis of variance level 5%. The results showed that four weed species consisted of three broad-leaved weed species, and one grass species were identified before land cultivation. At three weeks after planting, weeds' composition was nineteen consisting of fourteen broadleaves weed, one sedge, and four grass. At nine weeks after planting, the composition of nine species of weeds consisted of seven broad leaves, one nutsedge, and one grass. The presence of weeds reduced the yield of corn and green beans in the intercropping system.